Anális, diseño e implementación de un software para la administración y control utilizando la técnica de algoritmos genéticos para el estacionamiento "M&H" de la ciudad de Machala provincia de El Oro - Huanga Armijos, Maritza Fabiola (2013)
Proper control of a parking location in both vehicles entering; as well as proper management is one of the greatest needs in the garages of our environment as loa mostly performed manually; which it is why the system called "Analysis, design and implementation of software for the management and control technique using genetic algorithms for parking" M & H "of the city of Machala El Oro province." allowed to contribute to the optimization of resources, both material as humans are there in the parking "M & H" of the city of Machala El Oro Province, thanks to the use of the technique called Artificial Engineering: combining genetic algorithms quickly and efficiently.